La baronesa de Wilson: la doble marginalidad de una viajera decimonónica española - María Isabel Mena Mora (Cuadernos de Ilustración y Romanticismo, 2021)
This article analyzes the place of enunciation of decimononic traveler Emilia Serrano (Baroness of Wilson) as a double marginal subject —for being a woman and for being Spanish— as well as her strategies to build an emancipatory discourse. It examines the difficulties she raffled as a female traveler, but also the opportunities she knew how to take advantage of by writing from an «exceptional position». Serrano managed to insert her own interests and gender demands within the Catholic modernizing project and those voices seeking to defend Spain from the black legend. She also found a strategic potential when enunciating her discourse from within the Republic and Latin America, instead of doing it from within her homeland in the Old World.